Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.5858/2007-131-1033-aacocn
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Cost-Effectiveness of Core Needle Biopsy in the Evaluation of Suspected Lymphoma: A Study of 101 Cases

Abstract: Context.—Lymphomas have traditionally been diagnosed on excisional biopsies of lymph nodes in order to evaluate tissue architecture and cytomorphology. Recent lymphoma classification schemes emphasize immunophenotypic, genetic, and molecular aspects in addition to morphology as diagnostic features. Core needle biopsies are increasingly being used to obtain tissue for diagnosis in patients with lymphadenopathy and a clinical suspicion of lymphoma. These procedures are rapid, minimally invasive, well tolerated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 16 publications
2
29
2
7
Order By: Relevance
“…Previous studies have emphasized that low-volume tissue samples may avoid the need for surgical diagnosis in lymphoma. [25][26][27] Our results suggest the use of EBUS-TBNA inpatients with undifferentiated lymphadenopathy when lymphoma is a suspected diagnosis is reasonable, despite the necessity to proceed to a surgical diagnosis in a proportion of patients. It is likely that EBUS-TBNA may avoid both the morbidity and the financial costs associated with more invasive surgical procedures although it should be undertaken with the patient's understanding that further morphologic characterization of their disease by invasive surgical biopsy may be required.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have emphasized that low-volume tissue samples may avoid the need for surgical diagnosis in lymphoma. [25][26][27] Our results suggest the use of EBUS-TBNA inpatients with undifferentiated lymphadenopathy when lymphoma is a suspected diagnosis is reasonable, despite the necessity to proceed to a surgical diagnosis in a proportion of patients. It is likely that EBUS-TBNA may avoid both the morbidity and the financial costs associated with more invasive surgical procedures although it should be undertaken with the patient's understanding that further morphologic characterization of their disease by invasive surgical biopsy may be required.…”
Section: Discussionmentioning
confidence: 72%
“…The European Society for Medical Oncology has long considered surgical resection to be the gold standard biopsy method for staging ML due to the need for adequate tissue samples ( 36 ). However, in recent years, an increasing number of reports have shown that the diagnostic accuracy of subtype classification techniques using CNB is comparable to that of surgical resection ( 37 , 38 ), whereas CNB is superior to surgical resection in terms of the waiting period for examination, time required for the examination per se , invasiveness and medical costs ( 39 , 40 ). Both CNB and surgical biopsy of Ax LN specimens may be used to diagnose FL, with comparable results in terms of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasoundguided CNB can generally obtain a sufficient specimen and preserve the surrounding tissue structure, allowing immunohistochemistry analysis based on histomorphological examination, resulting in high diagnostic efficiency (6)(7)(8)(9). However, for lymph nodes with small short-axis diameters, the application of CNB is very limited and is associated with complications such as hemorrhage and nerve injuries (10,11). Cytological examination via ultrasound-guided FNA has the advantages of producing minimal trauma, simple and rapid execution (12), very good patient compliance and a low incidence of serious complications.…”
Section: Discussionmentioning
confidence: 99%